I do not walk alone: a path to remember and re-signify in the work of Paulo Nazareth - Silva, Camila Calolinda da; Alonso , Alex Fabiano; Ghizzi, Eluiza Bortolotto (Farol, 2021)
This article is interested in the work of contemporary artist Paulo Nazareth (1977). At first, he analyzes his artistic work through travel itineraries based on the concepts of anthropological “place” and “non-place”, coined by Marc Augé. Then, in order to deepen the study of the meanings with which the artist works, he dwells on a videographic record of the work “Árvore do Esquecimento” (2013), which he analyzes using an application of Peircean semiotics to the image, proposed by semiotician Lúcia Santaella. The results show a work that values the sense of place insofar as it goes against the figures of excess that Augé associates with non-places and, at the same time, symbolically reconstructs ancestral experiences of himself and of all the others with whom he identifies.